THE CORRELATION BETWEEN BENTHIC FORAMINIFERA AND SEDIMENT TYPES OF SOUTH MAKASSAR STRAIT - Sheilla Zallesa; Kresna Tri Dewi; Noor C.D. Aryanto (Marine Geological Institute of Indonesia, 2014)
South Makassar Strait is located between Kalimantan and Sulawesi Islands that is an important oceanographic pathway connecting between the Pacific and Indian oceans. This area is a part of sedimentary basin that has specific seabed morphology and sediment characteristics, including foraminifera as a component of sediments. The purpose of this study is to determine community structure of benthic foraminifera related to sediment characteristics. This study used 20 top core sediment samples from water depth between 200 and 1500 m. There are identified 38 species of benthic foraminifera and some of them are characterized the study area: Anomalinoides colligerus, Lenticulina suborbicularis, Planulina wuellerstorfi, , and Pseudonodosaria discrete. The diversity index is categorized as moderate values (1.0=H'= 3) and the average of evenness values is about 0.79. The dominance values are less than 0.5 indicate that there is no dominant species in the study area. In relation to sediment characteristics, it shows that the high abundance of benthic foraminifera occurs in sediment type of silty sand and sandy silt. Moderate abundance appears in sand following by low abundance in silt and sandy silt sediment types. Keywords: benthic foraminifera, community structure, sediment types and Makassar Strait Makassar bagian selatan terletak diantara Pulau Kalimantan dan Sulawesi yang merupakan jalur oseanografik yang penting menghubungkan Samudera Pasifik dan. Wilayah ini merupakan bagian dari cekungan sedimen yang mempunyai morfologi dasar laut dan karakteristik sedimen tertentu termasuk foraminifera sebagai komponen sedimen. Tujuan dari penelitian ini adalah untuk mengetahui struktur komunitas foraminifera bentik dalam kaitannya dengan tipe sedimen dasar laut. Penelitian ini menggunakan 20 sampel sedimen bagian atas dari pemercontoh inti pada kedalaman antara 200 dan 1500 m. Ada 38 spesies foraminifera bentik dan beberapa diantaranya mencirikan daerah penelitian: Anomalinoides colligerus, Lenticulina suborbicularis, Planulina wuellerstorfi, dan Pseudonodosaria discrete. Indeks keanekaragaman termasuk dalam kategori sedang (1,0=H’=3) dan nilai rata-rata keseragaman sekitar 0,79. Nilai dominasi lebih kecil dari 0,5 itu menandakan tidak ada spesies yang dominan pada lokasi penelitian. Terkait dengan karakteristik sedimen menunjukkan bahwa kelimpahan foraminifera bentik tinggi terdapat pada jenis sedimen pasir lanauan dan lanau pasiran. Kelimpahan sedang ditemukan pada jenis sedimen pasir diikuti kelimpahan rendah yang dijumpai pada sedimen lanau dan lanau pasiran. Kata kunci: foraminifera bentik, struktur komunitas, jenis sedimen, Selat Makassar.